Crystal Phase Conversion on Cobalt Oxide: Stable Adsorption toward LiO2 for Film‐Like Discharge Products Generation in Li‐O2 Battery. Issue 26 (31st May 2022) - Zhang, Shuting; Qiu, Jiachen; Zhang, Yu; Lin, Yuran; Liu, Rong; Yuan, Mengwei; Sun, Genban; Nan, Caiyun
Abstract: Regulating the structure and morphology of discharge product is one of the key points for developing high performance Li‐O2 batteries (LOBs). In this study, the reaction mechanism of LOB is successfully controlled by the regulated fine structure of cobalt oxide through tuning the crystallization process. It is demonstrated that the cobalt oxide with lower crystallinity shows stronger affinity toward LiO2, inducing the growth of film‐like LiO2 on the electrode surface and inhibiting the further conversion to Li2 O2 . The batteries catalyzed by the lower crystallinity cobalt oxide hollow spheres which pyrolyzed from ZIF‐67 at 260 °C (ZIF‐67‐260), go through the generation and decomposition of amorphous film‐like LiO2, which significantly reduces the charge overpotential and improves the cycle life. By contrast, the ZIF‐67 hollow spheres pyrolyzed at 320 °C (ZIF‐67‐320) with better crystallinity are more likely to go through the solution‐mediated mechanism and induce the aggregation of discharge product, resulting in the sluggish kinetics and limited performance. The combined density functional theory data also directly support the strong relationship between the adsorption toward LiO2 by the electrocatalyst and the battery performance. This work provides an important way for tuning the intermediate and constructing the high‐performance battery system. Abstract : A method for controlling the formation and decomposition of film‐like LiO2 through the regulated fine structure of cobalt oxide derived from ZIF‐67 hollow spheres to enhance the performance of Li‐O2 battery systems is reported. The inhibition of Li2 O2 formation and the enhancement in cycle life can be observed for batteries catalyzed by lower crystallinity cobalt oxide.